Utility of GATA3 in the differential diagnosis of pheochromocytoma. Issue 3 (5th June 2017) - Perrino, Carmen M; Ho, Alex; Dall, Christopher P; Zynger, Debra L
Abstract : Aims: GATA3 is a relatively new immunohistochemical marker which shows consistent nuclear expression in a variety of tumours, including breast and urothelial carcinoma. The staining pattern of GATA3 in adrenal lesions is not well established. We aim to describe the expression of GATA3 in adrenal tumours and determine if there is differential staining between pheochromocytoma and adrenal cortical carcinoma. Methods and results: A retrospective search was performed to identify 74 adrenal lesions which were tested immunohistochemically for GATA3 expression. GATA3 was negative in 90% of adrenal cortical carcinoma. In contrast, pheochromocytomas were frequently positive (71%), including benign pheochromocytoma, pheochromocytoma with features concerning for malignancy, malignant (metastatic) pheochromocytoma and composite pheochromocytoma with ganglioneuroma. Metastatic lung adenocarcinoma in the adrenal gland had occasional (36%) expression, while metastatic clear cell renal cell carcinoma in the adrenal gland did not express GATA3. Conclusion: As the most common pitfall in diagnosing adrenal cortical carcinoma is mistaking it for pheochromocytoma or vice versa, GATA3 may be useful in narrowing the differential diagnosis as a part of a panel of immunohistochemical markers. However, occasional GATA3 expression in the most common source of metastases within the adrenal gland, metastatic pulmonary adenocarcinoma, may confound the diagnosis due to the overlapping expression with pheochromocytoma and other carcinomas.